Effects of exogenous α-(1,4)-amylase on the utilisation of corn starch and glucose metabolism in broiler chickens - H. Zhou; Y. Wu; X. Sun; D. Yin; Y. Wang; T. Mahmood; J. Yuan (Animal, 2021)
Starch is the most important energy source in corn-based diets for broiler chickens, however, some proportion of dietary starch may be partially digested, leading to a decrease in feed utilisation. Therefore, supplementing exogenous amylase might be a feasible way to improve the utilisation of dietary starch for poultry. This study investigated the effects of exogenous α-(1,4)-amylase supplementation on the utilisation of corn starch and glucose metabolism in broiler chickens. A total of 560, 4-d-old Arbour Acres plus male broiler chicks were randomly divided into five treatment groups and fed a corn-soybean meal diet supplemented with 0, 400, 600, 800 and 1 200 U/kg α-(1,4)-amylase to evaluate growth. The growth performance, nutrient digestibility coefficients, digestive enzyme activity, glucose transporter transcription and cecal microbiota composition were evaluated in this study. Starch digestibility coefficient showed a quadratic response to α-(1,4)-amylase at 14 d and 42 d (P < 0.05). However, the endogenous α-amylase activity in jejunal content was linearly decreased (P = 0.045). Also, exogenous α-(1,4)-amylase linearly decreased ileal Na+-dependent glucose and galactose transporter 1 mRNA expression at 42 d (P < 0.001). Exogenous α-(1,4)-amylase generated higher insulin and glucagon serum concentrations in fasted birds (P < 0.05) and following re-feeding for 2 h (P < 0.001). BW gain and feed intake were strongly positively correlated with starch digestibility coefficient at both 14 d (r = 0.87) and 42 d (r = 0.91); whereas, the relative weight of the gizzard was weakly negatively correlated with starch digestibility coefficient (r = −0.35). The relative abundance of Unclassified_Bacillaceae was moderately positively correlated (r > 0.50) while Oscillospira, Ornithobacterium and Unclassified_Barnesiellaceae were moderately negatively correlated (−0.50 < r −0.39) with starch digestibility coefficient. In conclusion, exogenous α-amylase modulates metabolic function by increasing insulin and glucagon concentrations, influenced gut microbiota which may impact starch digestibility in the jejunum and ileum. The results of this study showed that excessive addition of exogenous α-(1,4)-amylase was not beneficial for the utilisation of starch in broiler chickens. Supplement more than 600 U/kg α-(1,4)-amylase inhibited glucose transporters, decreases the coefficients of starch and organic matter digestibility in the small intestine to a varying degree, thereby limiting the growth performance of broiler chickens.